Jonathan Edwards: Advice to Weary Theologians - Ross, Melanie C. (Scottish journal of theology, 2006)
This essay puts the issue of spiritual fatigue – those times when emotional despondency prohibits our wholehearted participation in worship – in conversation with Jonathan Edwards's public and private writings. Following an outline of the parameters for the discussion, Part I examines Edwards's Treatise Concerning Religious Affections. Although this was a treatise intended to trouble individuals who were overly confident in their religious affections, I suggest that when read through an alternative lens, Edwards's work offers comfort to those who struggle with their inability to ‘be present’ in worship. Edwards reminds us that religious affections have as much to do with constancy and disciplined habit as with fervour and immediacy of feeling.Part II takes a biographical turn, with particular interest in Edwards's Diary, Resolution, and Personal Narrative. Whereas Religious Affections stressed the necessity of self-discipline in religious practice, the twenty-year trajectory of Edwards's private writings reveals a subtle parallel emphasis: the need for patience and relinquishment in times of discouragement. Using insights from the public and private writings of Edwards, I conclude that times of spiritual fatigue call not only for constancy of practice but also for self-care and relaxation of heart.